2020
DOI: 10.1038/s41398-020-0797-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanism of SETDB1 in brain: implications for neuropsychiatric disorders

Abstract: Neuropsychiatric disorders are a collective of cerebral conditions with a multifactorial and polygenetic etiology. Dysregulation of epigenetic profiles in the brain is considered to play a critical role in the development of neuropsychiatric disorders. SET domain, bifurcate 1 (SETDB1), functioning as a histone H3K9 specific methyltransferase, is not only critically involved in transcriptional silencing and local heterochromatin formation, but also affects genome-wide neuronal epigenetic profiles and is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…there are several methyltransferases specific for H3K9 trimethylation, including SUV39H1, G9A, GLP, or SETDB1, among others (Zhang et al, 2020). In addition, SETB1 methyltransferase could also trimethylate H3 at lysine 9 (Zhu et al, 2020). On the other hand, histone H1 (Healton et al, 2020) and non-histone proteins, such as HP1 families (Lehnertz et al, 2003), could regulate such modification.…”
Section: Discussionmentioning
confidence: 99%
“…there are several methyltransferases specific for H3K9 trimethylation, including SUV39H1, G9A, GLP, or SETDB1, among others (Zhang et al, 2020). In addition, SETB1 methyltransferase could also trimethylate H3 at lysine 9 (Zhu et al, 2020). On the other hand, histone H1 (Healton et al, 2020) and non-histone proteins, such as HP1 families (Lehnertz et al, 2003), could regulate such modification.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by KRAB–ZFP interacting with SETDB1 in a sequence-specific manner after SETDB1 interaction with KAP1. KAP1 recruits SETDB1, as well as HP1 and the NuRD histone deacetylase complex [ 25 ]. The binding of SETDB1 to H3K9 is achieved via the three Tudor domains, which detect regions of H3 histones containing both K14 acetylation and K9 methylation [ 11 ].…”
Section: Biochemical Features Of Setdb1mentioning
confidence: 99%
“…SETDB1 is involved in heterochromatin formation and transcription silencing via histone H3 methyltransferase activity ( Zhu et al, 2020 ). In this study, we found that Setdb1 KD led to the upregulation of Nox4 and E2F1 .…”
Section: Discussionmentioning
confidence: 99%